2017
DOI: 10.1111/eff.12337
|View full text |Cite
|
Sign up to set email alerts
|

Growth potential and habitat requirements of endangered age‐0 pallid sturgeon (Scaphirhynchus albus) in the Missouri River, USA, determined using a individual‐based model framework

Abstract: An individual-based model framework was used to evaluate growth potential of the federally endangered pallid sturgeon (Scaphirhynchus albus) in the Missouri River. The model, developed for age-0 sturgeon, combines information on functional feeding response, bioenergetics and swimming ability to regulate consumption and growth within a virtual foraging arena. Empirical data on water temperature, water velocity and prey density were obtained from three sites in the Missouri River and used as inputs in the model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Yet, shifts in the availability or consumption of other prey that differ in nutrient content could affect nutrient ingestion by sturgeon or other fish that feed on benthic macroinvertebrates. Recent and ongoing studies have focused on examining abiotic factors that influence habitat use, prey consumption, and condition of YOY Scaphirhynchus sturgeons in the LMOR (Civiello et al 2018;Deslauriers et al 2018;Gemeinhardt et al 2019). However, understanding how other biotic factors may also be influencing recruitment and survival at age-0 still needs to be further understood.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, shifts in the availability or consumption of other prey that differ in nutrient content could affect nutrient ingestion by sturgeon or other fish that feed on benthic macroinvertebrates. Recent and ongoing studies have focused on examining abiotic factors that influence habitat use, prey consumption, and condition of YOY Scaphirhynchus sturgeons in the LMOR (Civiello et al 2018;Deslauriers et al 2018;Gemeinhardt et al 2019). However, understanding how other biotic factors may also be influencing recruitment and survival at age-0 still needs to be further understood.…”
Section: Discussionmentioning
confidence: 99%
“…Erwin et al, 2018;Sherman et al, 2007). A cooler thermal regime can increase the drift requirements of S. albus larvae by slowing down metabolic processes and the associated development rate (Braaten et al, 2008(Braaten et al, , 2012Deslauriers et al, 2017b;Kynard et al, 2007; this study). Indeed, larvae exhibited lower energy use and growth rate at cooler water temperatures that resulted in a slower behavioural transition from negative to positive rheotaxis (drifting to settling).…”
Section: Static Flowingmentioning
confidence: 81%
“…Impoundment of the Missouri River has resulted in a colder thermal regime (Braaten et al ., 2012; Heironimus, 2014; Figure 1) where the effects of cold hypolimnetic water releases below dams can suppress riverine temperatures for over 300 km downriver (DeLonay et al ., 2016; Erwin et al ., 2018; Sherman et al ., 2007). A cooler thermal regime can increase the drift requirements of S. albus larvae by slowing down metabolic processes and the associated development rate (Braaten et al ., 2008, 2012; Deslauriers et al ., 2017b; Kynard et al ., 2007; this study). Indeed, larvae exhibited lower energy use and growth rate at cooler water temperatures that resulted in a slower behavioural transition from negative to positive rheotaxis (drifting to settling).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have used small swim tunnels to measure the swimming performance of larval fish (Poulsen et al, 2012;Baker et al, 2014;Deslauriers et al, 2017) and other small organisms (Hata et al, 2017). Preliminary tests indicated that A. fulvescens yolk sac larvae do not exhibit consistent positive rheotactic behaviour (i.e.…”
Section: Materials and Methods Animal Husbandrymentioning
confidence: 99%